1996
DOI: 10.3177/jnsv.42.497
|View full text |Cite
|
Sign up to set email alerts
|

Content and Characteristics of Vitamin B12 in Some Seaweeds.

Abstract: SummaryThe vitamin B12 (B12) content in seven species of seaweed that are consumed frequently in Hokkaido, Japan, was microbiologically measured using Escherichia coil 215. Asakusanori (Porphyra tenera), maruba-amanori (Porphyra suborbiculata) and akaba-gin-nansou (Rhodo giossum pulcherum) showed higher B12 content than the other species, although the content varied greatly among samples in the same species. A bioautography on a thin-layer plate holding a mixture of silica gel and cellulose, differentiation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 9 publications
0
15
0
1
Order By: Relevance
“…These vitamin B 12 contents of the dried purple laver were markedly higher than those of other seaweeds (kelp, 0´1 mg, hijiki 0 mg, wakame, 0´6 mg; Resources Council, Science and Technology Agency, 1995); similar results have been reported by van den Berg et al (1988). Yamada et al (1997) reported that most of the vitamin B 12 in some seaweeds (wakame (Undaria pinnatifida) and akaba-gin-nansou (Rhodoglossum pulcherum)), may be cobamide-like vitamin B 12 analogues, which are inactive in mammals. Several studies have also reported that spirulina tablets (Spirulina sp.)…”
Section: Resultsmentioning
confidence: 99%
“…These vitamin B 12 contents of the dried purple laver were markedly higher than those of other seaweeds (kelp, 0´1 mg, hijiki 0 mg, wakame, 0´6 mg; Resources Council, Science and Technology Agency, 1995); similar results have been reported by van den Berg et al (1988). Yamada et al (1997) reported that most of the vitamin B 12 in some seaweeds (wakame (Undaria pinnatifida) and akaba-gin-nansou (Rhodoglossum pulcherum)), may be cobamide-like vitamin B 12 analogues, which are inactive in mammals. Several studies have also reported that spirulina tablets (Spirulina sp.)…”
Section: Resultsmentioning
confidence: 99%
“…(also known as nori) contain relevant amounts of Cbl ranging from 32.3 to 63.6 μg/100 g [179]. In vitro tests are promising, but there are not enough human clinical trials to consider the use of seaweed as favorable in vitamin provision [180,181]. In a clinical trial of six vegan children, the daily use of nori seaweed seemed to prevent Cbl deficiency, measured via serum Cbl [182].…”
Section: Vegetable Sources Of Vitamin B12 and Future Researchmentioning
confidence: 99%
“…The release of free Vitamin B 12 from the purple laver significantly decreased to approximately 2.5% at pH 7.0 (as a model of severe atrophic gastritis) [57]. Edible purple laver predominantly contains coenzyme forms (5′-deoxyadenosylcoblamin and methylcobalamin) of Vitamin B 12 or hydroxocobalamin (or both) [57,58,59]. …”
Section: Vitamin B12-containing Plant-derived Food Sourcesmentioning
confidence: 99%